Introduction to the Social Media + Society Special Issue on Selfies: Me-diated Inter-faces - Warfield, K.; Cambre, C.; Abidin, Crystal (SAGE PUBLICATIONS LTD, 2016)
This introduction to the special issue entitled Me-diated Inter-faces begins by bringing into question the concept of positioning: what is it that we are doing when we take a position within the study of social media? Reviewing the work of the inaugural manifestos of the journal Social Media + Society on one hand, and the introduction to the special issue on selfies for the International Journal of Communications on the other, this introduction provides both critical and creative in-roads for thinking and re-thinking digital self-images shared on social media. Given the constantly changing nature of social media, this paper is a call to researchers of social media to not fall prey to the ossification of our current positions since theorizing the “social” in social media means always at once theorizing the body. As such this intro offers numerous and diverse perspectives on the body that might inform emerging thoughts on the socially media body. The introduction then provides an overview of the papers in this special issue and concludes by offering openings and ruptures for further discussion, rather than closure of conclusions.